2011
DOI: 10.1021/ac201103e
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on Orthogonality Duality in Comprehensive Two-Dimensional Gas Chromatography

Abstract: The term "orthogonal" in comprehensive two-dimensional gas chromatography (GC × GC) has a double sided meaning as it stands for a separation resulting from the combination of two independent retention mechanisms (Giddings, J. C. J. High Resolut. Chromatogr. 1987, 10, 319) but also for a 2D separation where the components are evenly distributed over the entire 2D space. It is shown in the present study that a nonorthogonal GC × GC system associating a polar stationary phase in the first dimension (poly(ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
0
21
0
6
Order By: Relevance
“…To date, a common column combination used for environmental sample analysis in GC×GC/ToF-MS includes a non-polar GC-column in the first dimension followed by a more polar column in the second dimension 11, 14, 16,23,24,25 . In a previous study, this column combination resulted in good chromatographic separation and good space occupation for GC×GC/ToF-MS analysis of a coal liquefaction middle distillate sample containing semi-volatile organic compounds (SOCs) with different physicochemical properties, such as paraffins (alkanes), naphthenes (cyclic alkenes), aromatics and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a common column combination used for environmental sample analysis in GC×GC/ToF-MS includes a non-polar GC-column in the first dimension followed by a more polar column in the second dimension 11, 14, 16,23,24,25 . In a previous study, this column combination resulted in good chromatographic separation and good space occupation for GC×GC/ToF-MS analysis of a coal liquefaction middle distillate sample containing semi-volatile organic compounds (SOCs) with different physicochemical properties, such as paraffins (alkanes), naphthenes (cyclic alkenes), aromatics and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…[26] A separation-space evaluation method based on Denaulays triangulation algorithms was proposed by Semard et al, [27] and then further used to optimize the selection of column sets, geometric parameters of the secondary column, Even though non-polar polar column combinations are often stated as the preferred approach for GC GC, nonclassical conditions, that is, polar moderately non-polar column combinations [28] as well as liquid crystalline, [29] ionic liquid, [30] and enantioselective stationary phases, [31][32][33][34] are gaining attention and can lead to high-resolution and grouptype separations. Moreover, Omais and co-workers [35] recently suggested that the non-polar polar column combination is not a necessary condition to achieve large peak distribution in the 2D plane, and non-classical conditions can occasionally provide a large occupation of 2D space. Thus, there are no fixed rules for the combination of column-phase types.…”
Section: Structured Separation Space In Gc Gc Chromatogramsmentioning
confidence: 99%
“…Omais und Mitarbeiter [35] schlugen kürzlich vor, dass die unpolare polare Kombination stationärer Phasen keineswegs eine zwingende Voraussetzung für eine breite Signalverteilung im zweidimensionalen Trennraum ist. Nichtklassische Kombinationen kçnnen den Trennraum gelegentlich besser mit Signalen komplettieren.…”
Section: Strukturierter Trennraum In Gc Gc-chromatogrammenunclassified